Aggression in the academic workplace: a psychodynamic analysis of social work. Issue 3 (3rd July 2019) - Karpetis, George
Abstract: Aiming to promote quality collegial relationships in tertiary education, this theoretical study draws on the peer-reviewed literature to provide a psychodynamic analysis of workplace aggression in the social work discipline. Because the study assists academics to identify their aggressive practices and the aggressive practices of their colleagues, the findings can be of relevance to other practice-based disciplines. Elaborating on the causes and effects of the disciplinary, institutional and individual forms of aggression, this study identifies the avoidance of the emotional pain in work with clients as the main reason behind the active or passive–aggressive behaviours in the discipline. Academics act out this defensive manoeuvre through denying the existence of knowledge gaps in the discipline, denying the inextricable link between empirical research and theories of practice, teaching exclusively theories unsupported by empirical studies, and resisting to set boundaries on active and passive aggression. The study proposes the advancement of research-into-practice mindedness in social work schools, the requirement that prospective social work academics gain considerable practice experience before entering academia, the need for academic leadership positions to require peer-reviewed publications in both teaching and practice and the need for Schools to publish a volume of empirical research to be accredited as providers of social work education.